Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.21608/jppp.2015.74526
|View full text |Cite
|
Sign up to set email alerts
|

PHYSIOLOGICAL AND ULTRASTRUCTURE RESPONSES OF Schistocerca gregaria (FORSKAL) TO Metarhizium acridum AND FOUR BIO ACTIVE COMPOUNDS

Abstract: The effect of Metarhizium acridum and four bioactive compounds (Neem, L-Glutamic acid, Schinus molle and abamectin) in sole treatments and in combination with M. acridum was studied on the mortality of 5 th nymphal instar of desert locust Schistocerca gregaria as well as the time mortality responses and the ultra-structure of females ovary. The obtained results showed that mortality in case of Metarhizium acridum treatment reached to 100% after 14 days, while in case of neem treatment the mortality reached to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A. [37] who recorded the same increase in phenol oxidase parameters when treated S. littoralis larvae with neem oil after 2 days and they indicated that the insect immune response increase and attack these foreign particles.…”
Section: Effect On the 4 Th Instars Larvae Of A Ipsilonmentioning
confidence: 82%
See 1 more Smart Citation
“…A. [37] who recorded the same increase in phenol oxidase parameters when treated S. littoralis larvae with neem oil after 2 days and they indicated that the insect immune response increase and attack these foreign particles.…”
Section: Effect On the 4 Th Instars Larvae Of A Ipsilonmentioning
confidence: 82%
“…A. [37] who showed the same increase in phenoloxidase parameters when they treated S. littoralis larvae with neem oil after 2 days and they indicated that the insect immune response increase and attack these foreign particles. Also, the present results are in parallel with Santoyo, I. G. and Aguilar, A. C. [38] who stated that in invertebrate immunology have documented a complex array of host defenses.…”
Section: Effect On the 2 Nd Instar Larvaementioning
confidence: 83%